Pancreatic Pseudocyst with Mediastinal Extension Presenting as Pseudo-Kirklin Sign-Multimodality Imaging - Harshini Udayakumar; Venkatraman Indiran; Kalaichezhian Mariappan; Prabakaran Maduraimuthu (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
A mass lesion of the gastric cardia or fundus causing an alteration in the normal regular, translucent gastric fundal air shadow on a frontal erect chest radiograph is referred to as "the Kirklin sign." Here we present "Pseudo-Kirklin sign" observed on the frontal radiograph of a 46-year-old male patient due to a soft tissue shadow/contour deformity of the fundal gas shadow caused by pseudocyst of the pancreas. We evaluated the patient using plain radiography, contrast enhanced computed tomography, magnetic resonance imaging, and endoscopic ultrasound (EUS) with the cyst drained under EUS guidance. So far only two cases of mediastinal pseudocysts have been drained successfully by EUS-guided aspiration.